2020
DOI: 10.3390/biology9100329
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Factors Associated with High Concentration of Prostate-Specific Antigen: ELSIA Study

Abstract: Background: Prostate cancer (PC) is the second most common cancer among men, behind only non-melanoma skin cancer, and the main method of screening for PC is the prostate-specific antigen (PSA). To analyze the prevalence and the factors associated with high concentration of PSA in the elderly is essential to understand this outcome, and building strategies to decrease their rates of morbidity and mortality. Methods: We performed a cross-sectional study with 96 elderly men. A high level of PSA was defined by &g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…20 Higher PSA values (4 ng/ml or more compared with less than 4 ng/ml) were associated with PCa prevalence in our study, which had been con rmed in many other studies . 10,14 PSA was a single chain glycoprotein with serine protease activity synthesized and secreted by prostate acinar and duct epithelial cells. Under normal physiological conditions, PSA was mainly limited to prostate tissue, and serum PSA was maintained at a low concentration level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 Higher PSA values (4 ng/ml or more compared with less than 4 ng/ml) were associated with PCa prevalence in our study, which had been con rmed in many other studies . 10,14 PSA was a single chain glycoprotein with serine protease activity synthesized and secreted by prostate acinar and duct epithelial cells. Under normal physiological conditions, PSA was mainly limited to prostate tissue, and serum PSA was maintained at a low concentration level.…”
Section: Discussionmentioning
confidence: 99%
“…After venipuncture, the blood was stored, to be subsequently centrifuged in pairs for 10 min at 3000 rpm, and stored in an ice box and then transferred to the laboratory that performed the sample processing by immunoassay analyzer. 10 A PSA level equal to or greater than 4 ng/mL was considered high. 4…”
Section: Methodsmentioning
confidence: 99%
“…Few studies have looked at the isolated effect of diastolic BP on prostate cancer development, but among patients with prostate cancer with a mean age at diagnosis of 70 years, high levels of PSA were associated with high levels of systolic and diastolic BP 30 . In another study, a positive association between PSA and diastolic BP was observed when adjusting for age and other clinical and socioeconomic factors, 31 and a 5% increased risk for prostate cancer for each 11.4 mmHg increase in prediagnostic diastolic BP has been observed by others 32 …”
Section: Discussionmentioning
confidence: 99%
“…Contact was made with the older adults through home visits, informing them of the objectives, and requesting their participation in the research voluntarily. 20 In February 2020, 249 participants were excluded due to a lack of information (59 due to death, 36 due to relocation to another city, 18 due to refusal to participate, 25 due to not meeting the inclusion criteria, and 105 due to not being locatable); 48 were excluded because they already had dynapenia at the beginning of the study, and 6 were excluded due to a lack of information on handgrip strength, resulting in a final study population of 176 individuals (Figure 1).…”
Section: Participantsmentioning
confidence: 99%